Cementless primary total hip replacement: Four to eight year results with the Zweymüller-Alloclassic® prosthesis - Delaunay, C. (Springer-Verlag, 1998)
One hundred and twenty-nine consecutive cementless primary total hip arthroplasties with Zweymüller-Alloclassic® grit-blasted titanium components were evaluated prospectively at an average follow-up of 5.9 years. The clinical results were graded as excellent or good in 116 hips (90%), fair in 12, and poor in one due to a fracture of the femoral shaft at operation leading to early stem loosening and delayed ring loosening. Failure was defined as definite aseptic loosening, and the final survivorship at 8 years was 99.3% for the SL-stem, and 99.1% for the CSF-threaded cup. These early results compare favourably with those of total hip arthroplasties using new cementing techniques.